A bacteriophage JN02 infecting multidrug‐resistant Shiga toxin‐producing Escherichia coli: isolation, characterisation and application as a biocontrol agent in foods - Li, Ya‐Ke; Wu, Xin; Chen, Hu; Zhao, Yuan‐Yang; Shu, Mei; Zhong, Chan; Wu, Guo‐Ping (International journal of food science & technology, 2021)
Bacteriophages are increasingly considered as novel biocontrol agents against Multidrug‐resistant (MDR) Shiga toxin‐producing Escherichia coli (STEC). In this study, a virulent phage JN02 capable of infecting MDR STEC was isolated, characterised and evaluating its efficacy in reducing MDR STEC in foods. One‐step growth and stability assay showed that JN02 had a relatively short latent period (15 min), large burst sizes (69 PFU/cell), and high physicochemical stability (temperature (30–60°C), pH (2–11), 0.1%, 1% pig bile salt, biocides and food additives (100% chloroform, 0.1% acetic acid, 1% potassium sorbate). In spot tests, 18 E. coli strains were sensitive to JN02. In efficiency of plating (EOP), 4 E. coli strains were sensitive to JN02. Electron microscopy and genome sequencing showed that JN02 belongs to the family Myoviridae. Importantly, no known virulence‐associated, lysogenic and antibiotic genes were identified in the genome of JN02. Viable cell counts of MDR STEC were significantly (P < 0.05) reduced in milk (no viable counts) and beef samples (1.0–1.9 log10 CFU cm−2 reduction) when treated with JN02 at 4 °C. The results indicated that JN02 might be a new potential natural biological control agent for MDR STEC in foods. A lytic phage JN02 was isolated and identified as Myoviridae. No known virulence‐associated, lysogenic, and antibiotic genes were found in the genome of JN02, indicating that JN02 is safe. JN02 significantly reduced the content of Shiga toxin E. coli (STEC) in beef and milk, suggesting that JN02 might be a new potential natural biological control agent for STEC.